DAYA SAING PT BENAR FLORA UTAMA BERDASARKAN AKTIVITAS RANTAI NILAI FLORIKULTURA - Ratih Marina Kurniaty; Anas M. Fauzi; M. Achmad Chozin (School of Business, Bogor Agricultural University (SB-IPB), 2012)
ABSTRACTThe aims of this research were (1) to identify of the value chain that has been applied by the company, (2) to describe projections from internal and external condition as input in the company’s success factor analysis, (3) to determine the company’s strategic position, and (4) to formulate alternative strategies to increase the company’s competitiveness in floriculture industry. This research used SWOT analysis method by considering company’s position and value chain approach which was started with chain mapping to describe actors involved, what business issues in this company face and which activity has the greatest contribution. The value chain approach were also used to determine the prominent product based on the annual sales report. The research results indicated that the issues in the value chain include: expensive input prices, uncertainty in seed supply and higher transportation cost especially for Euro Country and America. Based on internal and external matrix, the company’s position is in the strategic growth quadrant, so the company can apply some alternative strategies such as (1) maintaining good relationships with customers and suppliers, (2) expanding market to Asia, (3) upgrading the types of tree, (4) attending big exhibitions, (5) develop products by creating plants trendcentre, (6) enhancing the knowledge management for the company’s human resource, (7) production maximizing for the domestic market, (8) establishing distribution channels in each city, (9) setting a clear target market, (10) maintaining the quality of the plants, (11) restructuring the company in order to clarify the specialization of work, and (12) designing documents to better provide the seeds according to customers’ need.Keywords: competitiveness, floriculture industry, chain mapping, value chain economic analysis, SWOT analysisABSTRAKTujuan penelitian ini adalah (1) identifikasi rantai nilai yang telah diterapkan oleh perusahaan, (2) menggambarkan dari kondisi internal dan eksternal sebagai analisis faktor keberhasilan perusahaan, (3) posisi strategis perusahaan, dan (4) merumuskan strategi alternatif untuk meningkatkan daya saing dalam industri florikultura. Penelitian ini menggunakan metode analisis SWOT dengan mempertimbangkan posisi perusahaan dan pendekatan value chain dimulai dengan pemetaan rantai untuk menggambarkan siapa aktor yang terlibat, apa masalah bisnis di perusahaan ini dan aktivitas mana memiliki kontribusi terbesar. Pendekatan rantai nilai juga digunakan untuk menentukan produk terkemuka dari laporan penjualan tahunan. Hasil penelitian menunjukkan bahwa isu-isu dalam rantai nilai meliputi: harga input yang mahal, pasokan benih tidak menentu dan biaya transportasi terutama untuk Negara Eropa dan Amerika lebih tinggi. Hasil matriks internal dan eksternal, posisi perusahaan pada pertumbuhan strategis sehingga perusahaan menerapkan beberapa strategi. Strategi alternatif yang dapat ditingkatkan oleh perusahaan, seperti: (1) maintaning hubungan baik dengan pelanggan dan pemasok, (2) memperluas pasar ekspor ke Asia, (3) meningkatkan jenis pohon, (4) mengikuti pameran besar, (5) berinovasi produk ke membuat trendcentre tanaman, (6) peningkatan manajemen pengetahuan untuk sumber daya manusia di perusahaan, dan (7) memaksimalkan produksi untuk pasar domestik, (8) saluran distribusi yang didirikan di setiap kota, (9) membuat target pasar yang jelas, (10) mempertahankan kualitas tanaman, (11) merestrukturisasi perusahaan dalam rangka untuk memperjelas spesialisasi pekerjaan, (12) membuat dokumen menyediakan benih sesuai dengan kebutuhan pelanggan.Kata kunci: daya saing, industri florikultura, rantai pemetaan, analisis rantai nilai ekonomi, analisis SWOT